Factors influencing activity-based adaptation practices of smallholder farmers towards climate impact in Malaysia - Shehu, Nabara Isah; Man, Norsida; Kamarulzaman, Nitty Hirawaty; Sulaiman, Zulkefly (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The oil palm in Malaysia has seen significant progress as it has turned into a huge industry. However, adverse climatic conditions are most prominent among the natural factors that are hindering the growth of the industry. Adaptation to climate change in agricultural settings depends on understanding farmers’ perceptions of climate impact, their support in adapting and the efficacy of adaptation practices. Such knowledge can improve adaptation strategies. This study addresses the limited understanding of how farmers appraise their activity-based adaptation practices and some influential factors. The study used a multi-stage sampling technique to select 382 oil palm farmers in Malaysia. The data were analyzed using descriptive statistics, Pearson correlation and multiple regression to identify significant factors contributing to activity-based adaption practices. Significant and positive correlation (p<0.01) existed between each variable and activity-based adaptation practices. Multiple regression analysis results showed that intention, extension services, and perceived impact were significant (p<0.05) determinants. The Adj.R2 value of 0.662 implies that three predictors explain about 66.2% of the variation in activity-based adaptation practices. The highest influence is attributed to perceived impact (β=0.888). The outcomes show that farmers’ attitude and social norms were not favourable towards activity-based adaptation practices. The technical competencies of the extension services should be improved in more than one programme towards farmers’ attitudinal change which is necessary for successful activity-based adaptation practices in Malaysia.